Cephalometric evaluation of children with nocturnal sleep-disordered breathing - Pirilä-Parkkinen, Kirsi; Löppönen, Heikki; Nieminen, Peter; Tolonen, Uolevi; Pirttiniemi, Pertti (European journal of orthodontics, 2010)
The present study aimed to assess the cephalometric features in children with sleep-disordered breathing (SDB). The subjects were 70 children (34 boys and 36 girls, mean age 7.3, SD 1.72, range 4.2–11.9 years) with habitual snoring and symptoms of obstructive sleep disorder for more than 6 months. On the basis of overnight polygraphic findings, the subjects were further divided into subgroups of 26 children with diagnosed obstructive sleep apnoea (OSA), 17 with signs of upper airway resistance syndrome (UARS), and 27 with snoring. A control group of 70 non-obstructed children matched for age and gender was selected. Lateral skull radiographs were taken and cephalograms were traced and measured. The differences between the matched groups were studied using t-test for paired samples. Differences between the subgroups were studied using analysis of variance followed by Duncan’s multiple comparison method. Children with SDB were characterized by an increased antero-posterior jaw relationship (P = 0.001), increased mandibular inclination in relation to the palatal line (P = 0.01), increased total (P = 0.019) and lower (P = 0.005) anterior face heights, a longer (P = 0.018) and thicker (P = 0.002) soft palate, smaller airway diameters at multiple levels of the naso- and oropharynx, larger oropharyngeal airway diameter at the level of the base of the tongue (P = 0.011), lower hyoid bone position (P = 0.000), and larger craniocervical angles (NSL–CVT, P = 0.014; NSL–OPT, P = 0.023) when compared with the non-obstructed controls. When divided into subgroups according to the severity of the disorder, OSA children deviated significantly from the control children especially in the oropharyngeal variables. Children with UARS and snoring also deviated from the controls, but the obstructed subgroups were not confidently distinguishable from each other by cephalometric measurements. Logistic regression analysis indicated that UARS and OSA were associated with decreased pharyngeal diameters at the levels of the adenoids (PNS–ad1) and tip of the uvula (u1–u2), an increased diameter at the level of the base of the tongue (rl1–rl2), a thicker soft palate, and anteriorly positioned maxilla in relation to the cranial base. Lateral cephalogram may thus reveal important predictors for SDB in children. Attention should be paid to pharyngeal measurements. Systematic orthodontic evaluation of SDB children is needed because of the effects of obstructed sleep on the developing craniofacial skeleton.